Peningkatan Pengetahuan Melalui Media Audio Visual Tentang Cara Mencuci Tangan yang Baik dan Benar pada Siswa Taman Kanak – Kanak Katolik St. Fransiskus Xaverius Pineleng - Ria Angelina Jessica Rotinsulu (Lembaga Pengembangan Kinerja Dosen, 2025)
Providing education on how to wash hands properly is an important effort to increase awareness of clean and healthy living, especially for young children. Children at this age are in a very rapid developmental stage, so the information and habits taught are more easily absorbed and formed into daily behavior. However, children's awareness and understanding of the importance of hygiene, especially handwashing, is still relatively low. Therefore, health education is essential to instill good habits from an early age. Washing hands with soap is one of the Clean and Healthy Lifestyle Behaviors (PHBS) that is effective in preventing the spread of various types of diseases, especially diseases transmitted through hands, such as diarrhea, ARI, and skin infections. PHBS about handwashing must be a habit applied in daily life, both in the family, school, and community environment. This educational activity was carried out at St. Francis Xaverius Pineleng Catholic Kindergarten with the aim of increasing knowledge and forming handwashing behavior according to the six recommended handwashing steps. The implementation method included providing educational materials, showing a video song that teaches the six steps of handwashing, demonstrations by the implementer, and direct practice by the children with movements and songs. The results of the activity showed an increase in children's knowledge and skills in washing their hands properly. The children demonstrated enthusiasm and active participation during the educational process. It is hoped that teachers and parents will continue to encourage children to practice hand hygiene to prevent illness and foster healthy lifestyles from an early age.